Pengelolaan Sampah Rumah Tangga di Kecamatan Dukuh Pakis, Kota Surabaya dengan Metode Life Cycle Assessment (LCA) - Mohamad Mirwan; Adienda Putri Olvianti (Prosiding ESEC, 2022)
The amount of waste generated in Dukuh Pakis District is 28,678 tons/day. The waste management system in Dukuh Pakis District tends to be disposed of directly into temporary containers in amixed state before being transported to temporary and final disposal sites. Identification and determination of household waste management scenarios is meeded to assess the environmental impact of the household waste processing process. The purpose of this study is to determine the environmental impact od the waste management scenario in Dukuh Pakis District. Data collection methods are observation, and garbage sampling. Meanwhile, data anlysis was carried out using Life Cycle Assessment (LCA) using the Center of Environmental Science of Leiden University Impact Assessment (CML-IA) method with SimaPro 9.3 software. Based on the result of the analysis, the weight values in Scenario 0 (existing) are 3,7 x 10-5, scenario 1 is 1,42 x 10-6, and Scenario 2 is 6,73 x 10-6. Based on the weighting results, scenario 1 has the lowest weighting value. Therefore, Scenario 1 is the best waste management system because the resulting environmental impact is low. Waste management in Scenario 1 includes, processing household waste by storing and sorting waste at the source, making compost, distributing waste for recycling, collecting and transporting the remaining waste to Benowo landfill.